(untitled) - Stone, Brad (New York, 2017)
The Upstarts is the definitive story of two new titans of business and a dawning age of tenacity, conflict, and wealth. In Brad Stone's riveting account of the most radical companies of the new Silicon Valley, we discover how it all happened and what it took to change the world.
Keywords: Thương mại điện tử,Electronic commerce,Doanh nghiệp kinh doanh mới,New business enterprises; Hoa Kỳ,United States